Ammonia sensor for point-of-care application. - Png, Shermaine. (2013)
Blood ammonia level when persistent at levels beyond the acceptable range of 40μM, can have detrimental effects to the human body such as liver dysfunction as well as damage of the central nervous system. Over the years, many techniques have been discovered to quantify ammonia in the body with the enzymatic method being the most popular technique of all. However, measurement of ammonia via this technique requires